2022
DOI: 10.1002/pon.6011
|View full text |Cite
|
Sign up to set email alerts
|

A rural‐urban comparison of self‐management in people living with cancer following primary treatment: A mixed methods study

Abstract: Objective: To investigate and compare self-management in people living with cancer following treatment, from rural and urban areas in the United Kingdom where there is a significant evidence gap. Methods:A cross-sectional explanatory sequential mixed methods design. This involved a self-completion questionnaire that collected data on demographics, self-management using the PAM-13 and rural-urban residence and 34 in-depth interviews that aimed to explore and compare the barriers and facilitators to selfmanageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
(141 reference statements)
0
9
0
Order By: Relevance
“…Not surprisingly, the majority of the research that was included in this review was conducted in North America and Australia which is similar to pre-pandemic scholarship on rurality and cancer that has been dominated by these areas for the past decade [ 11 , 12 , 13 , 15 , 16 , 17 , 18 , 31 , 34 ]. Only two of the COVID-19 studies that were included in this rapid review were from the European continent with one of these being from the UK where there is now a small but increasing body of pre-pandemic research that considers the impact of rurality on cancer experiences and outcomes [ 30 , 32 , 33 ]. Future research that looks at cancer and geographic residence, particularly that in the UK, should extend out to include coastal areas which are amongst the most deprived in the country and there is now a shifting policy focus to reduce growing health inequalities in deprived coastal communities [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not surprisingly, the majority of the research that was included in this review was conducted in North America and Australia which is similar to pre-pandemic scholarship on rurality and cancer that has been dominated by these areas for the past decade [ 11 , 12 , 13 , 15 , 16 , 17 , 18 , 31 , 34 ]. Only two of the COVID-19 studies that were included in this rapid review were from the European continent with one of these being from the UK where there is now a small but increasing body of pre-pandemic research that considers the impact of rurality on cancer experiences and outcomes [ 30 , 32 , 33 ]. Future research that looks at cancer and geographic residence, particularly that in the UK, should extend out to include coastal areas which are amongst the most deprived in the country and there is now a shifting policy focus to reduce growing health inequalities in deprived coastal communities [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that there are a range of characteristics belonging to rural communities that can positively influence the experiences of cancer survivors who reside in rural areas [ 25 , 26 , 27 ]. For example, people living in rural communities frequently report more close relationships with family and friends and sometimes have access to greater levels of community support and green spaces which can improve both physical and mental health [ 15 , 28 , 29 , 30 ]. Rural cancer survivors can have unique values and different attitudes to help-seeking as well as maintaining a stronger degree of stoicism [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that urban–rural residence and sex were neither barriers nor facilitators to self‐care (Okpalauwaekwe et al., 2022). In contrast, another study in the United Kingdom investigating the urban–rural differences in self‐management in people living with cancer revealed that rural participants were significantly more active in self‐management than their urban counterparts (Nelson et al., 2022). The urban and rural differences in self‐care in Chinese older adults with MCCs remain understudied.…”
Section: Introductionmentioning
confidence: 93%
“…Rates of pandemic related anxiety, depression, posttraumatic stress disorder, psychological distress, and stress across the general population [24] [25,26], saw increased mental health service demand. This demand and reductions in service delivery due to COVID-19 controls, forced service providers to pivot rapidly to telehealth to maintain care delivery.…”
Section: The Impact Of the Covid-19 Pandemicmentioning
confidence: 99%